2010
DOI: 10.1111/j.1751-7915.2009.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the field of high‐molecular‐weight polycyclic aromatic hydrocarbon biodegradation by bacteria

Abstract: SummaryInterest in understanding prokaryotic biotransformation of high‐molecular‐weight polycyclic aromatic hydrocarbons (HMW PAHs) has continued to grow and the scientific literature shows that studies in this field are originating from research groups from many different locations throughout the world. In the last 10 years, research in regard to HMW PAH biodegradation by bacteria has been further advanced through the documentation of new isolates that represent diverse bacterial types that have been isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
100
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(108 citation statements)
references
References 313 publications
(592 reference statements)
3
100
3
2
Order By: Relevance
“…PAHs Cycloclasticus [36,42,43,73] Pyrene Mycobacterium [25,41,72] one basking alkanes and phytane in 21 days was 47.29 and 41.21 %, respectively [64]. Yuan et al also found the degradation rate of branched hydrocarbons was nearly two times than that of n-alkanes hydrocarbons [77].…”
Section: The Degradation Rate Of Branched Hydrocarbons Is Significantmentioning
confidence: 99%
“…PAHs Cycloclasticus [36,42,43,73] Pyrene Mycobacterium [25,41,72] one basking alkanes and phytane in 21 days was 47.29 and 41.21 %, respectively [64]. Yuan et al also found the degradation rate of branched hydrocarbons was nearly two times than that of n-alkanes hydrocarbons [77].…”
Section: The Degradation Rate Of Branched Hydrocarbons Is Significantmentioning
confidence: 99%
“…Production of indigo from exogenous indole was assessed by adding a crystal of indole to the lids of inverted Petri plates containing sRB2-pyruvate medium 24 h after inoculation. Indigo production from indole is indicative of activity for some ring-hydroxylating dioxygenases involved in the initial step in the aerobic degradation of PAHs [24,25]. A purple colour developed by colonies on the plate after exposure to indole confirmed the likely presence of an active ring-hydroxylating dioxygenase.…”
mentioning
confidence: 98%
“…Because of its versatile PAH degradation ability, M. vanbaalenii PYR-1 has been extensively studied as a model at both the laboratory and field scales (16, 17). These efforts have produced considerable information on its metabolic, biochemical, physiological, and molecular characteristics, which are also found in other aromatic-compound-degrading bacteria (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Because of its versatile PAH degradation ability, M. vanbaalenii PYR-1 has been extensively studied as a model at both the laboratory and field scales (16, 17). These efforts have produced considerable information on its metabolic, biochemical, physiological, and molecular characteristics, which are also found in other aromatic-compound-degrading bacteria (16)(17)(18)(19)(20)(21)(22).A global PAH metabolic network (MN) in M. vanbaalenii PYR-1 has been proposed on the basis of genomic, proteomic, metabolic, and biochemical information (23). The PAH-MN describes the biochemical pathways for the biodegradation of 10 PAHs with 183 metabolites and 224 chemical reactions, providing systematic insight into the structure, behavior, and evolution of bacterial PAH metabolism.…”
mentioning
confidence: 99%